A Novel Methodology for the Determination of Optimal Locations for the Establishment and Performance Assessment of Integrated GNSS CORS and SAR Corner Reflector Networks in the Advent of GGOS - Kakoullis, Dimitris (My University, 2024)
This doctoral thesis is intrinsically linked to the Cyprus Continuously Operating Natural Hazards Monitoring and Prevention System, abbreviated CyCLOPS, a national strategic research infrastructure devoted to systematically studying geohazards in Cyprus and the EMMENA region. To date, the permanent segment of CyCLOPS is comprised by six permanent sites, each housing a Tier-1 GNSS continuously operating reference stations (CORS) co-located with two calibration-grade corner reflectors (CRs). The latter are strategically positioned to account for both the ascending and descending tracks of SAR satellite missions, including ESA's Sentinel-1. The goal of CyCLOPS is to establish a reliable permanent station network across Cyprus, featuring co-located GNSS and SAR CR configurations that continuous monitoring geohazards. To fulfil this goal, it is essential to determine the most suitable sites for the permanent installation of equipment, which guarantees the best performance of each device that utilizes associated space-based technologies. Thus, a comprehensive literature review was conducted to analyze such infrastructures, the required instruments according to international standards, installation procedures, and the optimal spatial distribution of stations to create an integrated nationwide network capable of providing combined data of the two advanced space-based technologies, with maximum performance and minimal error. Nonetheless, the review identified fragmented guidelines regarding the co-location of SAR and GNSS permanent infrastructures. Furthermore, no guidelines exist for the determination of the most suitable locations using a holistic approach, in terms of criteria and required data.
Keywords: CYCLOPS; Infrastructures; GNSS CORS; Quality Control; Corner Reflectors; Point Target Analysis; Visibility Analysis; Multi-Criteria Decision Analysis